2012
DOI: 10.1186/1756-0500-5-446
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of poor quality of life and predictors of health related quality of life in cirrhosis at a tertiary care hospital Pakistan

Abstract: BackgroundCirrhosis produces variety of symptoms which eventually lead to a negative impact on Health Related Quality of Life (HRQOL). The general aim of this study was to evaluate the magnitude of poor HRQOL and to assess factors related with HRQOL in patients with CLD in Pakistan.FindingsThis was a cross sectional study conducted in gastroenterology outpatient clinics of Aga Khan University Hospital, Karachi on adult patients with cirrhosis. In this study chronic liver disease questionnaire (CLDQ) was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 23 publications
(36 reference statements)
3
31
2
1
Order By: Relevance
“…This may have led to the amelioration of HRQOL and ALB through improved liver function. Previous studies have also reported an association between ALB and HRQOL in patients with hemodialysis patients or liver cirrhosis (25,26). Similar results were shown in this study.…”
Section: Discussionsupporting
confidence: 82%
“…This may have led to the amelioration of HRQOL and ALB through improved liver function. Previous studies have also reported an association between ALB and HRQOL in patients with hemodialysis patients or liver cirrhosis (25,26). Similar results were shown in this study.…”
Section: Discussionsupporting
confidence: 82%
“…There are concordant results in other similar studies regarding the average age of participants, gender, marital status, and educational status [8,[15][16][17]. Significant predominance of males in different etiologic groups is consistent with the data from literature.…”
Section: Discussionsupporting
confidence: 82%
“…Also, our results are in orchestra with literature data, and indicate higher frequency of males within the group of alcoholic liver disease patients. This was not the case with the CLD of other etiology, where the distribution by gender was significantly more uniform compared to the previous studies [16][17][18].…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations